Maturitas Agama; Konsep Solusif dalam Lintas Agama dan Budaya: (Tinjauan Psikologis Pendidikan Islam) - Fitriah M. Suud (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2018)
Talking about Islamic education conceptually and theoretically is undoubtedly. Many arguments in the Qur'an and Hadith explained the purposes and scopes of Islamic education. There were numerous values and more than eighteen grades of characters, which were discussed by educational leaders. Islam respected the values of peace and tolerance in religion, thus, Muslims can live in diversity and plurality in Indonesia, which is not only different in religions and beliefs but also different in tribes, cultures and languages. However, the understanding of values and concepts is not enough to ensure realization of peace, yet it needs maturity in religion. The process to achieve maturity also requires guidance and habituation especially against adolescents who have trouble in looking for identity. Therefore, it is necessary to seek a solution for this problem. The purpose of this article is to describe how the conditions of religious life in the homeland that have relation to inter-religious and cultural. Furthermore, it may give solution to realize the maturity of religion for adolescents in high school and college, because this young generation will determine the climate of peace in the country.